Seasonal and diel patterns in activity and habitat use by brook trout (Salvelinus fontinalis) in a small Newfoundland lake - D. Cote; B. Tibble; R. A. Curry; S. Peake; B. K. Adams; K. D. Clarke; R. Perry (Environmental Biology of Fishes, 2020)
Despite the challenges winter poses to salmonids inhabiting temperate and northern environments, there are relatively few studies that evaluate the factors that influence activity and habitat use during this season, particularly for lake environments that are ice-covered. This study examines brook trout depth distribution and movement (activity and range) in relation to temperature, light, and time of day across a 17-month period in a small lake in Newfoundland, Canada. Brook trout maintained elevated diurnal activity patterns throughout the year, despite seasonal changes in temperature, shifts in depth use, and prolonged, ice-induced darkness. Despite the tendency for relatively lower activity at night, brook trout remained active nocturnally, inferring a shift in foraging modes rather than a cessation of feeding. Winter movement velocities and ranges were less than other seasons but they occupied littoral areas that overlapped extensively with spring and fall core ranges. In contrast, summer core ranges of brook trout were principally comprised of areas with cooler water in the deep portion of the lake. As water temperature increased, daytime movement velocities increased in a log-linear fashion, whereas modeled nighttime movement velocity relationships with temperature were curvilinear and included the lowest movement velocities at 2–3 °C and the highest at the extremes of the occupied temperature range. The ability of brook trout to maintain diurnal activity patterns throughout a wide spectrum of environmental conditions suggests a strong behavioral and physiological capacity to adapt to their seasonally variable environment.

Female mediation of sperm competition in the millipede Alloporus uncinatus (Diplopoda: Spirostreptidae) - M. Barnett; S. R. Telford; B. J. Tibbles (Behavioral Ecology and Sociobiology, 1995)

Female mediation of sperm competition in the millipede Alloporus uncinatus (Diplopoda: Spirostreptidae) - M. Barnett; S. R. Telford; B. J. Tibbles (Behavioral Ecology and Sociobiology, 1995)